Assessment of the Full Compatibility of Copper(I)‐Catalyzed Alkyne‐Azide Cycloaddition and Oxime Click Reactions for bis‐Labelling of Oligonucleotides. Issue 2 (10th December 2014) - Estalayo-Adriàn, Sandra; Lartia, Rémy; Meyer, Albert; Vasseur, Jean-Jacques; Morvan, François; Defrancq, Eric
Abstract The conjugation of oligonucleotides with reporters is of great interest for improving their intrinsic properties or endowing new ones. In this context, we report herein a new procedure for the bis‐labelling of oligonucleotides through oxime ligation (Click‐O) and copper(I)‐catalyzed alkyne–azide cycloaddition (Click‐H). 5′‐Azido and 3′‐aldehyde precursors were incorporated into oligonucleotides, and subsequent coupling reactions through Click‐O and Click‐H (or vice versa) were successfully achieved. In particular, we exhaustively investigated the full compatibility of each required step for both tethering strategies. The results demonstrate that click Huisgen and click oxime reactions are fully compatible. However, whilst both approaches can deliver the targeted doubly conjugated oligonucleotide, the route involving click oxime ligation prior to click Huisgen is significantly more successful. Thus the reactions investigated here can be considered to be key elements of the chemical toolbox for the synthesis of highly sophisticated bioconjugates.